Research Advances in Cardio-Cerebrovascular Diseases of Ligusticum chuanxiong Hort. - Li, Dan; Long, Yu; Yu, Shuang; Shi, Ai; Wan, Jinyan; Wen, Jing; Li, Xiaoqiu; Liu, Songyu; Zhang, Yulu; Li, Nan; Zheng, Chuan; Yang, Ming; et al. (Frontiers in Pharmacology, 2022)
Cardio-cerebrovascular diseases (CVDs) are a serious threat to human health and account for 31% of global mortality. Ligusticum chuanxiong Hort. (CX) is derived from umbellifer plants. Its rhizome, leaves, and fibrous roots are similar in composition but have different contents. It has been used in Japanese, Korean, and other traditional medicine for over 2000 years. Currently, it is mostly cultivated and has high safety and low side effects. Due to the lack of a systematic summary of the efficacy of CX in the treatment of CVDs, this article describes the material basis, molecular mechanism, and clinical efficacy of CX, as well as its combined application in the treatment of CVDs, and has been summarized from the perspective of safety. In particular, the pharmacological effect of CX in the treatment of CVDs is highlighted from the point of view of its mechanism, and the complex mechanism network has been determined to improve the understanding of CX’s multi-link and multi-target therapeutic effects, including anti-inflammatory, antioxidant, and endothelial cells. This article offers a new and modern perspective on the impact of CX on CVDs.